Can Exercise Reduce the Autonomic Dysfunction of Patients With Cancer and Its Survivors? A Systematic Review and Meta-Analysis - Lavín-Pérez, Ana Myriam; Collado-Mateo, Daniel; Mayo, Xián; Liguori, Gary; Humphreys, Liam; Jiménez, Alfonso (Frontiers in Psychology, 2021)
Cancer therapies have increased patient survival rates, yet side effects such as cardiotoxicity and neurotoxicity can lead to autonomic nervous and cardiovascular systems dysfunction. This would result in a parasympathetic and sympathetic activity imbalance. Heart rate variability (HRV), which reflects autonomic modulation, is a valuable physiological tool because it correlates with cancer-related fatigue, stress, depression and mortality in cancer patients. To analyze the effects of exercise programs on the autonomic modulation, measured by the HRV, of cancer patients and survivors. The PRISMA guidelines were followed, and the quality of the articles was assessed with the PEDro scale. The meta-analysis statistic procedure was performed by using Revman 5.3 software. Results: From the 252 articles found, six studies were included in the review involving 272 participants aged 30 to 75 years. Exercise programs had a mean length of 10.4 ± 4.6 weeks, a frequency of 3 ± 1.4 days/week, and a mean duration of 78 ± 23.9 minutes. In time-domain HRV measures, exercise may increase in standard deviation of normal to normal intervals (p<0.00001, with a mean difference (MD) of 12.79 ms from 9.03 to 16.55) and a decreased root mean square of successive RR interval differences (p=0.002, with a MD of 13.08 ms from 4.90 to 21.27) in comparison to control groups. Frequency domain data reveal that exercise group improve significantly more than the control groups in low-frequency (absolute power: p<0.0001, with a SMD of 0.97 from 0.61 to 1.34; relative power: p=0.04, with a MD= -7.70 from -15.4 to -0.36), high-frequency (absolute power: p=0.001, with a SMD of 1.49 from 0.32 to 2.66; relative power: p=0.04, with a MD of 8.00 nu from 0.20 to 15.80) and low-to-high frequency ratio (p= 0.007 with a MD of -0.32 from -0.55 to -0.09). Exercise programs could lead to positive effects on the autonomic modulation of cancer patients and survivors. More beneficial changes may occur with resistance and endurance workouts. However, due to the low number of interventions further research is needed to substantiate our findings and to provide insights regarding the exercise intensity required to improve patient’s autonomic modulation.